PERENCANAAN GELAGAR BENTANG 30 METER JALAN LAYANG (FLYOVER) PADA PERSIMPANGAN GADANG KOTA MALANG - Kurniawan, S,Pd MT, Achendri M; Rocman, Taufiq; Poerwanto, johanes Asdhi (Prokons: Jurnal Teknik Sipil, 2019)
The purpose of this thesis is to complements the feasibility study of flyover building which is otherwise feasible. The feasibility will be continued to flyover structure plan. The flyover located in the Intersection of Gadang Highway Malang City is planned to have a total length of 290 meters and a width of 8 meters with a bridge division of 20 meters and 30 meters.The method used to plan is LRFD (Load Resistance Factors Design) and loading based on SNI 2016. For statics analysis STAAD Pro v8i program is used. In the 30-meter span bridge girder modeling in the STAAD Pro V8i program there are 2 ways of modeling that is by using a beam model and using a plate model. By making comparisons between the two methods.The results are obtained: The girder with beam model uses 4D22 in compressive reinforcement, 14D25 in flexural reinforcement, 10D13 in side reinforcement and Ã˜10-200 in shear reinforcement. The girder with plate model uses 5D25 in compressive reinforcement, 16D29 in flexural reinforcement, 8D19 in side reinforcement and Ã˜10-200 in shear reinforcement.